Adobe Animate CC 2017 : - Galesso, Michael
The Adobe Animate is a professional multimedia authoring and animation program that is developed by Adobe Systems. It was formerly known as Macromedia Flash, FutureSplash Animator and Adobe Flash Professional. This program is used to design vector graphics and animations that can be used for online video, television programs, web applications video games and rich internet applications. It was originally created to be the main authoring environment for the Adobe Flash platform producing vector based software and interactive content. It was changed to Adobe Animate in 2016 to better show the position of the market since many of the Animation now uses HTML5.